(untitled) (Texas Journal of Medical Science, 2025)
The review considers the possibilities of predicting preeclampsia (PE) and its complications, modern criteria for diagnosing hypertensive gestational disorders, as well as the tactics of their intensive therapy. Particular attention is paid to providing anesthetic support during operative delivery in patients with PE and its complications